Environmentally friendly photoactive heterojunction zinc tin oxide nanoparticles. Issue 2 (1st February 2016) - Ivetić, T.B.; Finčur, N.L.; Abramović, B.F.; Dimitrievska, M.; Štrbac, G.R.; Čajko, K.O.; Miljević, B.B.; Đačanin, Lj.R.; Lukić-Petrović, S.R.
Abstract: Heterojunction zinc tin oxide (ZnO/SnO2 ) nanoparticles were prepared using a top–down traditional solid-state method; mechanical grinding followed by annealing, and characterized by X-ray diffraction, multi-wavelength excitation Raman scattering, scanning electron microscopy, diffuse reflectance and photoluminescence spectroscopy. The photocatalytic degradation kinetics of amitriptyline in the presence of the obtained ZnO/SnO2 nanoparticles under simulated solar and UVA irradiation was determined and used as a model reaction for understanding the photocatalytic mechanism when such mixed oxide semiconductors are used in removing the pharmaceutically active compounds from wastewaters.